PENGARUH FISIKOLOGI RASA AMAN SOSIAL PENGHARGAAN DAN AKTUALISASI DIRI TERHADAP KINERJA KARYAWAN PT DALIJO ULAM UPADI DI MUARA BADAK - Nasution, Aliciar Amalia; Abdullah, Rahim; Aryani, Farida (I-Con Media, 2022)
In an effort to realize optimal performance with quality human resources CV. Dalijo Ulam Upadi makes various efforts to motivate employees, one of which is by providing compensation, namely basic salary (monthly) and bonuses. However, from the information that researchers received based on reports from other employees, there are several symptoms that occur in some employees, such as a lack of employee work enthusiasm, including being often late, often missing work hours and employees being slow in completing work, even though this is still considered a problem. which is light but will be detrimental to the company if this is allowed to drag on. For this reason, researchers really want to provide motivation that is based on the application of several theories put forward by experts, whether they can be implemented or not so that workers are enthusiastic about carrying out their work, do not miss work hours and arrive on time because they have been well motivated through several of these methods. This study aims to determine the effect of physiology, security, social, respect and self-actualization simultaneously and partially on employee performance on the CV. Dalijo Ulam Upadi in Muara Badak. The sample in this study were employees at CV. Dalijo Ulam Upadi, amounting to 27 people. The data analysis technique of this research is multiple regression, with hypothesis testing using the f test and t test. And the results of the research obtained are simultaneously and partially the five variables of this study include physical, social security, appreciation and self-actualization variables that have a significant effect on employee performance at CV Dalijo Ulam Upadi in Muara Badak.